Fluctuation in the Income of Rubber Farmers in Tingkea’o Village: The Contribution of Production Costs and Selling Price - Emilia Margaretha Ngkolu; Selmita Paranoan; Rahayu Indriasari; Ernawaty Usman (Jurnal Ilmiah Global Education, 2026)
This study aims to analyze the contribution of production costs, particularly fertilizer and pesticide costs, as well as the selling price of rubber sap to the income fluctuations of rubber farmers in Tingkea'o Village, North Morowali. Using a quantitative descriptive analysis approach with SEM PLS analysis processed through WarpPLS V.8.0 software. Data were collected from 34 rubber farmers randomly through structured interviews, direct observation, and documentation. The results show that fertilizer and pesticide costs contribute significantly and positively to rubber farmers' income, with path coefficients of 0.419 and 0.342, respectively (p-value < 0.001). Conversely, the selling price has no significant effect (p-value = 0.205). The independent variable model explains 41.5% of the variation in income, with the remainder influenced by other external factors. This study reinforces the farming theory of optimizing production costs to improve farmers' livelihoods, while also revealing the limited influence of selling prices due to market structure and the role of middlemen. The strategic recommendations provided can form the basis for policies to support the development of sustainable rubber farming and improve the welfare of farmers in the region.